Training and Work Environment Enhance Employee Performance (Case Study: Coal Mining Company in East Kalimantan) - Iswanto Iswanto; Ferren Azzagha Putri; Lucia Rini Sugiarti; Fendy Suhariadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
AbstractThe success of a business greatly depends on the presence of human resources with high competency and technical skills, supported by optimal performance. To achieve the goals planned by the company, all necessary requirements and infrastructure must be prepared to support the achievement of its targets and planned efforts. Competent human resources and a supportive and conducive work environment significantly contribute to the performance achievements of a company. This study employs a quantitative approach, with questionnaires as the primary tool for collecting data from respondents. The study focuses on mechanics working for contractor companies in the coal mining sector, located in East Kalimantan. The research was conducted using the random sampling method, involving a total of 115 respondents from coal mining contractor companies. Data analysis was carried out using multiple linear regression techniques, assisted by SPSS version 27 software. In 2024, the performance of coal mining contractor projects was recorded to be lower compared to other contractor locations. This situation serves as the background and primary reason for conducting this research on coal mining contractor companies. The results of the study indicate that training has a positive and significant effect on performance achievement, with additional support from the work environment. These findings underline the critical role of employee training and a supportive work environment in driving performance improvements, as observed in coal mining contractor companies in Kalimantan.